Dynamic modeling and analysis of flexible micro-porous piezoelectric sensors applicable in soft robotics - Ghadami, Ali; Mirdamadi, Hamid Reza; Khanbareh, Hamideh (Frontiers in Electronic Materials, 2022)
With recent advances in system integration technologies, numerous efforts have been made to develop soft piezoelectric sensors for various engineering and healthcare applications. Using flexible and sensitive materials is crucial for designing soft sensors in order to maximize their efficiency and integrability. Micro-porous PU-PZT composite is a recently designed piezoelectric particulate composite material with an improved flexibility and piezoelectric voltage coefficient over common piezoelectric ceramics that makes it a promising candidate for application in soft sensors. In this study, we investigate the dynamic response and sensitivity of the micro-porous PU-PZT composite for applications in soft sensors in both 33 and 31 modes using energy methods. By using the effective field method, the micro-porous PU-PZT composite material properties were extracted and optimized based on the partially experimentally measured properties in order to get a complete picture of the properties of the material. In addition, the effects of changing the sensor geometry by varying the thickness and adding an extra layer between the piezoelectric layers are studied. Finally, a large area sensor based on micro-porous PU-PZT composite is simulated in COMSOL, and the effect of several parameters on sensor’s performance is investigated. Dynamic analysis of the sensor shows high sensitivity in both 31 and 33 modes which is a significant improvement compared to the commonly used bulk piezoelectric ceramics. This work has demonstrated that due to the high output voltage and structural flexibility of the micro-porous PU-PZT composite, a flexible large-area sensor would be a suitable choice for artificial skins and smart gloves.